The Two-Way Appropriation of Indigenous Knowledge: Environmental Management Policies and the Laponia Process - Nilsson Dahlström, Åsa (Journal of Northern Studies, 2010)
In the face of climatic changes and environmental problems, indigenous knowledge is increasingly being accepted as an alternative to Western science in conservation policies. While indigenous knowledge may help indigenous empowerment, it is also placed under the control of the authorities whose science and structures it is meant to challenge. Indigenous knowledge is therefore the subject of a two-way appropriation by indigenous peoples as well as environmental authorities. This process is illustrated by the Sami reindeer herders in the World Heritage site of Laponia in Arctic Sweden, who are negotiating a new joint management scheme with Swedish authorities, including a Sami majority on the park board. Sami indigenous knowledge will form the basis for the new management policies, but with minimal changes to existing national legislation. While the Sami will gain some political control, Swedish authorities will also gain access to and control over Sami indigenous knowledge, hence a two-way appropriation.